International students’ perspectives on social-emotional competences in the context of an intervention study - Yausheva, Almira (My University, 2024)
In recent years, internationalisation and globalisation have significantly influenced the movement of people, information, policies, and knowledge, driving the expansion of international higher education. This study focuses on international students enrolled in English-medium international programmes in Finland, which are inherently multicultural and bring together individuals from diverse backgrounds. While this diversity enriches the learning environment, it also presents emotional and interpersonal challenges in adapting to new systems and contexts and navigating cultural differences. Social-Emotional Learning (SEL) has been shown to enhance collaboration and learning effectiveness by improving academic and career success, fostering positive attitudes and behaviours, enhancing interpersonal relationships, and promoting well-being. This research aims to explore students' thinking on social-emotional competences within the context of a short-term SEL intervention during the introductory course of an international master’s degree. Thematic analysis was employed to examine the qualitative responses of nine participants across three surveys, conducted at different stages of the intervention, with the aim of providing insights into the intervention’s outcomes. The results of this study illustrate that students found cultural differences influencing their communication and self-regulation, highlighting the importance of considering these factors when designing SEL programmes in an international setting. The intervention appeared to foster students’ awareness and reflection on social-emotional competencies. Participants particularly showed awareness in communication-related aspects and were able to reflect on multiple challenges and contextual factors connected to all three competences. Moreover, participants noted that the reflection diary as a beneficial tool for developing emotional awareness together with verbal discussion of their emotions. In conclusion, the researcher argues that the implementation of SEL programmes should extend beyond the school level to higher education institutions, especially in international programmes where students face unique challenges in adapting to new systems and contexts and navigating cultural differences.
Keywords: social emotional learning, emotional awareness, interpersonal communication, self-regulation, international students, university, postsecondary education, multicultural education, intervention